Влияние пониженных доз некоторых инсектицидов на репродуктивную систему колорадского жука (Leptinotarsa decemlineata Say) - Сикура, А.И.; Сикура, Л.В.; Требесова, Р.М. (Вестник зоологии, 1972)
Study of the effect of decreased doses of preparations of organosynthetic insecticide group: chlororganic — DDT, polychloropinene and phosphororganic — chlorophos on reproductive system of Leptinotarsa decemlineata S a y showed that they affect insect gametogenesis differently. The stimulating effect of chlorophos is stronger than that of DDT and polychloropinene.